The Relationship Between Work Stress And Nurse Shift Work With The Implementation Of Patient Safety In The Inpatient Room Of Porsea Hospital During The Covid-19 Pandemic - Dosmaida Nababan; Tumpal Manurung; Tamara Hutahaean (CV. AFDIFAL MAJU BERKAH, 2023)
Nurses as one of the health workers who handle Covid-19 patients feel the impact of stress because they face unusual situations, The increase in Covid-19 patients can cause nurses to become stressed and at risk of making mistakes. Each hospital has different work shifts, irregularities in work shift schedules in nurses can cause errors in the provision of nursing care and patient application. The purpose of this study was to determine the relationship between work stress and nurse shift work in the Inpatient Room of RSUD Porsea during the Covid-19 pandemic. This research method uses descriptive analytics with a cross-sectional design, which was carried out at Porsea Hospital, Toba Regency, data collection was carried out in February 2022. Sampling is a total sampling of 48 respondents. The results of the chi-square test obtained a p-value of 0.022 < 0.05, meaning that there is a significant relationship between work stress and patient safety application and p-value 0.011 < 0.05, This means that there is a significant relationship between work shifts and the application of patient safety. The recommendations of this study for hospital management need to pay attention to the mental state of nurses and manage work shifts effectively during the Covid-19 pandemic.